Mechanical and thermal properties of lightweight concrete incorporated with activated carbon as coarse aggregate - Chin C.O.; Yang X.; Kong S.Y.; Paul S.C.; Susilawati; Wong L.S. (Elsevier Ltd, 2023)
Activated carbon; Aggregates; Agricultural wastes; Compressive strength; Concrete mixtures; Light weight concrete; Palm oil; Porous carbon; Tensile strength; Thermal conductivity; Water absorption; Activation process; Coarse aggregates; Elevated temperature; Mechanical and thermal properties; Oil palm; Porous structures; Splitting tensile strength; Water penetration; Concrete aggregates